An overview of occupational accidents notification systems within the enlarged EU - Guedes Soares, C.; Fialho, T.; Antão, P.; Silva, S.A. (Work: A Journal of Prevention, Assessment and Rehabilitation, 2011)
This paper describes a comparative analysis of the official forms used for reporting occupational accidents within the EU-27 member states. The comparison is based on two analysis grids (coding schedule) created to that effect, which incorporate a set of evaluation criteria and an interpretation key. The results obtained in the analysis allowed for attention to be drawn to the relevant attributes of such forms in terms of their content and format/structure. It also revealed the main similarities and differences between each country, providing a complete assessment of the 27 member states. The discussion gives account of the level of implementation of the "new" Eurostat variables within the European Statistics of Accidents at Work (ESAW). Furthermore, the study shows that certain formats (structure of information fields) appear to facilitate completeness of the information collected. It has also demonstrated that the European harmonisation process is still far from completion, although the newcomer states seem to be adjusting quickly to the process. The findings of this study may bring useful insights to national authorities and European policy-makers, or to employers/enterprises wishing to implement their internal procedures aligned with the ESAW methodology. The scientific community is another interest group, whose research relies on official statistics, preferably comparable across all countries.